Comparison of CORE and PBL Learning Models Based on Students' Mathematics Learning Outcomes - Farman Farman; Nurlinda Sari; Marniati Marniati (JME (Journal of Mathematics Education), 2022)
This study aims to determine (1) students' mathematics learning outcomes in the Connecting, Organizing, Reflecting, and Extending (CORE) model, (2) students' mathematics learning outcomes in the problem-based learning model (PBL), (3) comparison of the effectiveness of the learning model CORE and PBL based on learning outcomes. The type of this research is experimental research. Samples were taken using random cluster sampling in class IX students of SMP Negeri 03 Poleang. The results obtained are class IX.A with 20 students as the class utilizing the CORE model and class IXB with 21 students as the class using the PBL model. Data retrieval is done through a test technique to obtain data on students' mathematics learning outcomes. The research data were analyzed using descriptive and inferential statistical methods. The average value of students' mathematics learning outcomes in the CORE model is 83.9, while the value of PBL class mathematics learning outcomes is 77.3. Inferentially, hypothesis testing using t-test obtained tcount = 2.743 ttable = 1.685 with a significant level = 0.05, indicating a significant difference in mathematics learning outcomes between students taught by the CORE and PBL learning models. Thus, applying the CORE learning model is more effective than applying the PBL model in terms of students' mathematics learning outcomes